2012
DOI: 10.1111/j.1365-2702.2012.04255.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of aggressions suffered by healthcare workers as predictors of burnout

Abstract: The survey showed evidence of a double process: (1) by which excess workload helps predict burnout, and (2) by which a mismatch in the congruence of values, or interpersonal conflict, contributes in a meaningful way to each of the dimensions of burnout, adding overhead to the process of exhaustion-cynicism-lack of realisation. Relevance to clinical practice.  Studies indicate that health professionals are some of the most exposed to disorders steaming from psychosocial risks and a high comorbidity: anxiety, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 19 publications
7
68
1
11
Order By: Relevance
“…(11) In this sense, the managements of mental health services should develop strategies locally, so users can exercise their citizenship regarding the freedom to smoke and the respect to non-smokers. Frequently, in these spaces there are no areas reserved for smokers, turning non-smokers into passive smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) In this sense, the managements of mental health services should develop strategies locally, so users can exercise their citizenship regarding the freedom to smoke and the respect to non-smokers. Frequently, in these spaces there are no areas reserved for smokers, turning non-smokers into passive smokers.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that professionals working in hospitals had higher scores of depersonalization and nurses working in community services had a greater sense of personal fulfillment. (5)(6)(7)(8)(9)(10)(11)(12) The exposure to conflict situations and living with violence in the workplace can contribute to the psychological burden on nursing professionals. A protective measure against the violence of patients can be implemented by the service management with appropriate therapeutic support.…”
Section: Discussionmentioning
confidence: 99%
“…Os acidentes com perfurocortantes, durante a manipulação do material e agressões físicas (44,52,54) são identificados como cargas mecânicas, já a exposição a material biológico, em casos de acidentes de trabalho, evidencia a carga biológica (24) . A carga química é descrita durante a exposição dos profissionais de enfermagem a agentes químicos e poluição ambiental (22,34) .…”
Section: Categoria 2 -Condições De Trabalho Que Predispõem àS Cargas unclassified
“…Outros fatores estão relacionados com o trabalho noturno, que perturba o equilíbrio oxidanteantioxidante e/ou gera estresse oxidativo (9) nos trabalhadores, assim como o sofrimento (10,14,15,52) , síndrome de Burnout (34,37,40,44,50) entre os profissionais de enfermagem e o aumento do risco de acidentes (21) de trabalho. A implantação de um novo sistema de turnos de trabalho, visando uma melhor distribuição de carga horária, possibilitaria uma redução no número de ausências no trabalho (35) .…”
Section: Categoria 3 -Influências Das Cargas De Trabalho Na Saúde Do unclassified
“…A fizikai agresszió közül leggyakrabban (53%) a rúgás, ütés, valamint a pofon fordult elő [13]. Gascón és mtsai által vizsgált 1826 spanyol egészségügyi dolgozó 11%-át bántalmazták fizikálisan legalább egyszer, és 34,4%-át fenyegették meg legalább egyszer egy év alatt [14]. Amerikában, Oregon államban, házi betegápolók kö-rében készült felmérésben a válaszadók 51,5%-a tapasztalt szóbeli agressziót, 27,6% szexuális zaklatást, összes-ségében a válaszadók 61,3%-a tapasztalt egy év alatt valamilyen agresszív eseményt munkája során [5].…”
Section: Agresszió Az Egészségügyi Dolgozók Körébenunclassified